2015
DOI: 10.1155/2015/462469
|View full text |Cite
|
Sign up to set email alerts
|

Distention of the Immature Left Ventricle Triggers Development of Endocardial Fibroelastosis: An Animal Model of Endocardial Fibroelastosis Introducing Morphopathological Features of Evolving Fetal Hypoplastic Left Heart Syndrome

Abstract: Background. Endocardial fibroelastosis (EFE), characterized by a diffuse endocardial thickening through collagen and elastin fibers, develops in the human fetal heart restricting growth of the left ventricle (LV). Recent advances in fetal imaging indicate that EFE development is directly associated with a distended, poorly contractile LV in evolving hypoplastic left heart syndrome (HLHS). In this study, we developed an animal model of EFE by introducing this human fetal LV morphopathology to an immature rat he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Responses to pathologic stimuli such as allotransplantation [16,17] and ischemia-reperfusion injury [18] are also assumed to be different from those of mature adult hearts. By using the present models with modifications, we have shown that an immature heart responds differently upon being exposed to severe distention and develops endocardial fibroelastosis, a unique form of cardiac fibrosis developing on the endocardial surface predominantly in immature hearts [12]. In addition, in the current study we observed that the transplanted neonatal heart developed a rather thickened LV wall after 2 weeks of mechanical unloading.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Responses to pathologic stimuli such as allotransplantation [16,17] and ischemia-reperfusion injury [18] are also assumed to be different from those of mature adult hearts. By using the present models with modifications, we have shown that an immature heart responds differently upon being exposed to severe distention and develops endocardial fibroelastosis, a unique form of cardiac fibrosis developing on the endocardial surface predominantly in immature hearts [12]. In addition, in the current study we observed that the transplanted neonatal heart developed a rather thickened LV wall after 2 weeks of mechanical unloading.…”
Section: Discussionsupporting
confidence: 50%
“…We have been studying effects of mechanical load on the immature heart through a heterotopic neonatal rat heart transplantation model [11,12,13]. A specific procedural strategy with several technical refinements was required to overcome innate vulnerability of using neonatal animals as donors.…”
Section: Introductionmentioning
confidence: 99%
“…Although sub-myocardial ischaemia has been proposed as a cause of EFE, analysis of coronary vasculature in HLHS has not supported this proposal [ 32 , 33 ]. Recent studies have suggested that EFE results from excessive or ectopic endocardial to mesenchymal transformation [ 34 , 35 ]. It is unclear whether this is therefore a specific element in the pathogenesis of this phenotype, in contrast to the miniaturised or slit-like ventricles, or represents a situation where there is reduced but present flow, signalling EFE formation as a secondary response.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats have provided further support linking impaired hemodynamics and impaired ventricular function to endocardial defects. Thus, distention of the left ventricle caused by surgically induced aortic regurgitation was shown to lead to endocardial injury and endocardial fibroelastosis [30]. We have already cited the studies in the developing chick that show decreased flow across the mitral valve subsequent to ligation of the left atrium can produce a variant of left ventricular hypoplasia [8].…”
Section: The Endocardium In the Setting Of Hypoplastic Left Heart mentioning
confidence: 99%